Measurement and Comparison of Signal Levels of GSM900, GSM1800 and UMTS Bands - Mustafa CANSIZ; Teymuraz ABBASOV; M.Bahattin KURT; A.Recai CELIK (International Journal of Applied Methods in Electronics and Computers, 2016)
Signal levels of GSM900, GSM1800 and UMTS bands were measured as mobile on the main streets in the city center of Diyarbakır at the same time and route during a week. The measurements were performed by using high precision and portable spectrum analyzer with an isotropic electric field antenna and a laptop. The high precision spectrum analyzer is a device that measures the high frequency electromagnetic fields. The isotropic electric field antenna allows a three axis measurements. The laptop was used to record and analyze the measurement samples. Electric field strengths were measured as signal levels in this study. Some statistical parameters such as standard deviation and variance were calculated with 95% confidence interval for measurement samples. The highest signal levels were measured as 3.8580 V/m for GSM 900 band, 2.9440 V/m for GSM1800 band and 6.0900 V/m for UMTS band during a week. Similarly, mean electric field strength values as average signal levels were calculated as 0.4985 V/m for GSM 900 band, 0.2350 V/m for GSM1800 band and 0.6281 V/m for UMTS band. According to the mean electric field strength values, the average signal levels of three bands were ranked as UMTS, GSM900 and GSM1800 from the largest to the smallest, respectively. The highest variation in standard deviation and variance was observed on Wednesday for GSM900 and UMTS bands and Thursday for GSM1800 band.